PENGARUH DISIPLIN KERJA DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN - Lestari, Sri; Afifah, Dilla (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effect of work and training on employee performance (a case study at PT Ardena Artha Mulia in the production section). The number of samples is 50 employees, all of which are respondents in this study. The data technique used a questionnaire, the data were analyzed using the SPSS version 25 program. The analysis performed was regression and regression analysis, coefficient of determination, f test, and t test. Based on the results of hypothesis testing partially work discipline has no effect on employee performance with a significance level of 0,108 > 0,05 and tcount 1,639 < 1,678. Partially job training has a positive and significant effect on employee performance with a significance level of 0,000 < 0,05 and tcount 5,112 > 1,678. The coefficient of determination (R2) for the work discipline variable is 0,317, meaning that it provides a contribution of the influence of work influence on employee performance by 31,7% and the remaining 68,3% from other factors such as: compensation, motivation, leadership style, and others. The coefficient of determination (R2) for the job training variable is 0,536, meaning that it provides a contribution of the effect of training on employee performance by 53,6% and the remaining 46,4% is influenced by other factors such as: work